3D numerical simulation of the separation zone at the channel–pipe junction - Bin Sun; Linqin Feng; Zhiwei Li; Zhanqi Song; Cheng Li (Water Science and Technology, 2023)
At the confluence zone, the separation zone affects the flow, pollutant transport, and damages the bed and sidewalls of the channel. In this research, the geometric characteristics of the separation zone and the tailwater effect at the 90° channel–pipe junction are investigated using experiments and numerical simulations. These characteristics are different from the previous study in the channel or river junctions. (1) The separation zone is not attached to the sidewall of the channel. The shape of the separation zone is close to an ellipse but there is depression at the inside of the separation zone. (2) There is a pair of helical cells with opposite flow directions near the sidewall, which affects the shape of the separation zone and results in the differences. (3) The volume of the separation zone is proportional to the discharge ratio and the water-surface height. Furthermore, it's found that the momentum ratio is the basic reason affecting the volume of the separation zone. (4) The tailwater effect is affected by the discharge ratio and the water-surface height. And there is a significant positive correlation between the volume of separation zone and tailwater effect. HIGHLIGHTS The characteristics of separation zones at channel–pipe junction are researched, which are rarely studied.; The shape of the separation zone and circulation flow is totally different from the previous studies.; The correlation between the separation zone and the tailwater effect is verified in this research.;